2021
DOI: 10.1101/2021.07.19.452920
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The angiotensin antagonist Losartan modulates social reward motivation and punishment sensitivity via modulating midbrain-striato-frontal circuits

Abstract: Social deficits and dysregulations in dopaminergic midbrain-striato-frontal circuits represent transdiagnostic symptoms across psychiatric disorders. Animal models suggest that modulating interactions between the dopamine and renin-angiotensin system with the angiotensin receptor antagonist Losartan (LT) can modulate learning and reward-related processes. We have therefore determined the behavioral and neural effects of LT on social reward and punishment processing in humans. A pre-registered randomized double… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 94 publications
1
4
0
Order By: Relevance
“…The current pattern of results may reflect modulatory effects of RAS blockade on dopaminergic neurotransmission given that LT has been shown to induce stronger D1 receptor expression (46) which has been associated with better reward-associative learning (47). These findings resonate with recent studies reporting an LT-induced enhancement of learning from positive relative to negative events (12) as well as an LT-induced shift from preferential social punishment towards social reward processing (17). Together, this pattern of effects suggests that LT can attenuate the impact of negative information thus promoting motivation to select rewarding options.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The current pattern of results may reflect modulatory effects of RAS blockade on dopaminergic neurotransmission given that LT has been shown to induce stronger D1 receptor expression (46) which has been associated with better reward-associative learning (47). These findings resonate with recent studies reporting an LT-induced enhancement of learning from positive relative to negative events (12) as well as an LT-induced shift from preferential social punishment towards social reward processing (17). Together, this pattern of effects suggests that LT can attenuate the impact of negative information thus promoting motivation to select rewarding options.…”
Section: Discussionsupporting
confidence: 91%
“…Seventy right-handed healthy male Chinese participants were screened according to evaluated enrollment criteria (see Supplemental Methods, sample size based on previous studies [15][16][17]). The study focused on male individuals to control for sex differences in response to RAS blockade [22] and menstrual cycle-dependent variations in reward processing [23].…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Growing evidence from animal models and human findings have suggested a crucial role of the renin-angiotensin system (RAS) in emotion and memory formation which may overlap with processes relevant for the development of PTSD (1517). Different lines of research have indicated an important role of the RAS in the development of PTSD such that (1) blood levels of renin were elevated in individuals with trauma-experience (18), (2) treatment with angiotensin blockers, particularly the angiotensin II type 1 receptor antagonist losartan (LT) during trauma exposure reduced the incidence of PTSD (19, 20), and (3) administration of LT in healthy controls also reduced autonomic stress reactivity during experimental trauma induction (21) and shifted emotional reactivity from negative to positive information (22, 23). While these findings support that targeting the RAS via LT may prevent the development of PTSD by modulating emotional or memory formation processes, the underlying behavioral and neurobiological mechanisms have not been examined.…”
Section: Introductionmentioning
confidence: 99%